Study of the Porosity of the Tiles out of Vibrated Mortar by Microstructural Analysis - TOUKOUROU, CHAKIROU A.; BAGAN, GONTRAND COMLAN; TCHEHOUALI, DÈFODJI ADOLPHE; VAUTRIN, Alain (My University, 2014)
The promotion and the popularization of the micro concrete tiles in any locality obligation with a will of durable development pass by a standard of quality, which is based on the results of scientific and technical research taking account of local specificities. This work proposes to study the porosity of the micro concrete by micro structural analysis. From this study, it comes out that the variation of porosity compared to the ratio of the fine gravels (s/(s + g)) is decreasing. Indeed more the granular ratio increases less low is the density of pores of material. The decrease of porosity according to the granular rate is not infinite; it tends towards a minimum starting from a rate of fine gravel close to 50%. The results obtained justify well the ratio of fine gravel practised by tileries.
Keywords: Micro Concrete Tile; Porosity; Micro Structural Analysis; G Volume of Fine Gravel; S Volume of Sand; 1.